Perbandingan Kurikulum Indonesia dengan Kurikulum Perancis - Dilva Hardila; Novia Rahayu (ScienceEdu, 2024)
The education system in each country is different and has its own characteristics according to the conditions of the country that are not owned by other countries. There are some countries that have very advanced education, but many are moderate and very slow in their development. Historically, the state largely determines its education system, which can be seen from the country's educational policies and politics. Then it is also influenced by the geography of a country, the potential of natural resources and its financial policies. So far, there are countries that have made education the main goal so that the largest percentage of the state budget is used for education. And they even put teachers in very high positions with high salaries. France is one of the most advanced countries in terms of education among other European countries. France has also become a destination for education in the world so that thousands of students from all over the world are visited. In this article, we try to compare the education system in France with that in Indonesia. The aim is to take the positive values that exist in France and then apply them in Indonesia according to Indonesia's own conditions and potential. However, it will be difficult for us to match the education system in France.